ANALISIS KELAYAKAN PENGEMBANGAN PRODUK BUBUK JAMBU GETAS MERAH (Psidium Guajava Linn) - , HAYUNINGTYAS PUSPITASARI; , Dr. M. Affan Fajar Falah, STP., M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Red guava have known as types of fruit that contain with high vitamin C. It is believed to increase the trombosit as well. Red guava contain calory, vitamin A, vitamin B1, vitamin C, calcium, carbohidrate, phospore, zink, protein, fat and water. One of the region which has a high productivity of red guava is Kendal. However, the production process of red guava in this region is limited, so that in harvest time the price of red guava become low and many guava will be damaged because its self life is short. The aims of this research are to give the alternative way for production process by producing guava powder, to identify quality standard of guava powder based on SNI traditional baverage powder in aluminium foil package during storage, to predict the self life of the product, and to know financial feasibility from this product development. The characteristic of the product is examined by using the organoleptic test (flavor, smell, colour, texture) and the laboratory test ( water content, ash content, fat, carbohidrate, protein, fiber, total sugar, vitamin C, metal contamination, microbial kontamination and sulfit residu). The prediction of self life is analysed by using ASLT (Accelerated Self Life Testing) Arrhenius method. The result shown that the best processing method in producing red guava powder is cabinet dryer. The quality parameter of red guava powder is in accordance with SNI, except in water content parameter. There are characteristic changes during storage such as the degradation of pH, the increasing of aw , and the degradation of colour change. According to water activity (aw) ,the prediction of self life is 30 days for red guava powder with additional citric acid and 29 days for red guava powder without additional citric acid. Based on financial analysis, this product development is feasible and profitable.